Design and validation of an academic cyberloafing scale in university students - Pereyra Girardi, Carolina Iris; Mur, Julian Andres; Cirami, Lautaro (Revista Ecos de la Academia, 2025)
The accelerated adoption of technologies in education has driven academic interest in cyberloafing, exploring its impact on student behavior related to the use of the Internet during classes. This paper aims to design and validate an academic cyberloafing scale in Argentine university students. An exploratory factor analysis (EFA) was performed using polychoric correlations. The sample consisted of 310 university students from Argentina. Kaiser-Meyer-Olkin adequacy index = .780 and Bartlett’s test of sphericity x² =3428.9, p<.00001 were calculated. For the EFA, the unweighted least squares (ULS) method was applied with a Promin rotation method, and a four-factor solution was chosen, which explained 69% of the variance (daily life 43%, exchange 10%, work 9% and education 7%). Ordinal α was calculated for each factor: daily life = .928, education = .956, work = .925 and exchange = .945. The constant transformations in the field of technologies raise the challenge of making updated psychometric adaptations that reflect current behaviors. It is recommended that future lines of research confirm the proposed factorial structure, consider the impact of new behaviors linked to technology such as artificial intelligence and focus on Latin American populations.